SemUr - Semantic Databases for Uralic Languages - Hämäläinen, Mika (Zenodo, 2018)
These databases are translated from SemFi by using Giellatekno XML dictionaries. The included python script can be used to update these databases or to create new ones for other languages. Currently, SemUr has the following languages SemSms - Skolt Sami SemKpv - Komi Zyrian SemMyv - Erzya SemMdf - Moksha Cite as Hämäläinen, Mika. (2018). Extracting a Semantic Database with Syntactic Relations for Finnish to Boost Resources for Endangered Uralic Languages. In The Proceedings of Logic and Engineering of Natural Language Semantics 15 (LENLS15)